Particle sampling in boilers of waste incineration plants for characterizing corrosion relevant species. (September 2016) - Schumacher, Stefan; Lindermann, Jörg; Stahlmecke, Burkhard; Khot, Amit; Zeiner, Thomas; van der Zwaag, Till; Nordsieck, Hermann; Warnecke, Ragnar; Asbach, Christof
Graphical abstract: Highlights: Development of a novel probe for particle sampling in boilers of MSWI. Disturbing sampling artifacts such as salt condensation are largely suppressed. The evolution of the particle phase in the course of the boiler is characterized. Especially particles of several micrometers contain high chlorine fractions. Abstract: A novel probe has been developed to characterize particles in boilers of waste incineration plants, which are under suspicion to essentially drive the corrosion processes. The probe collects larger particles on impaction plates and smaller particles on membranes, whose deposition characteristics have been studied by computational fluid dynamics. Artifacts by condensation of salt vapors are largely suppressed. The size distribution, morphology and chemical properties of the particles can be investigated by scanning electron microscopy and energy-dispersive X-ray spectroscopy. The probe has been employed for measurements in a waste incineration plant to characterize the aerosol on its way through the boiler.